Effect Of Liquid Smoke And Carrageenan To Beef Meatball Texture And Lightness - Widayat, Widayat; Afriani, Nurfika (Indonesia Journal of Halal, 2021)
AbstractBeef meatballs lots sold in the market with additional preservatives that are not recommended for food. This study will discuss the use of liquid smoke to preserve beef meatballs with the addition of carrageenan as firmness agent. The purpose of this study was to determine the optimum composition of addition of liquid smoke and carrageenan. Beef meatballs prepared by adding liquid smoke and carrageenan on a particular variation into meatballs dough. Liquid smoke variation used was 0.5%-1%, and carrageenan variation used was 0.5%-1.5%. The meatballs that has been created and then stored for 0, 12, 24, and 36 hours. The results of optimization using RSM shows the maximum value of hardness and springness of beef meatballs obtained in 24 hours of storage. The optimum composition of liquid smoke and carrageenan on the hardness and springness obtained on the liquid smoke concentration 0.755% and 1.04% carrageenan. The addition of carrageenan in beef meatballs provide a dominant influence on the texture. Lightness test is not a significant effect on the addition of liquid smoke and carrageenan, but give significant effect on the storage time, the longer the storage time, the lightness of the color of beef meatballs was decrease